Chromatographie ionique avec déctecteur conductométrique et électrochimique couplés: application au dosage des nitrite, nitrate, chlorure et sulfate - V. Kordorouba; M. Pelletier; A. Balikungeri; W. Haerdi (CHIMIA)
Selective determination of nitrite ions while in the presence of chloride, nitrate and sulfate ions was obtained using ion-exchange chromatography coupled with conductimetric and electrochemical detectors. Advantages and applications of this method are described.